(untitled) (UNIZIK Journal of STM Education, 2024)
The study investigated the effect of metacognitive instructional strategy (MIS) on secondary school students’ academic achievement in geometry in Idemili North Local Government Area of Anambra State. Two research questions and three null hypotheses tested at 0.05 level of significance guided the study. The study adopted a quasi-experimental pre-test post-test nonrandomized control group design. Ninetyeight (98) senior secondary one (SS1) students from two co-educational government owned secondary schools in Idemili North were sampled from a population of 3363 using purposive and simple random sampling techniques formed the sample for the research. Achievement Test on Geometry (ATOG) constructed by the researcher containing 50 multiple choice questions was used to collect data on students’ academic achievement in geometry. The ATOG and lesson plans were validated by three experts, one from measurement and evaluation and two from science education all from Nnamdi Azikiwe University, Awka. Kudder-Richardson Formula 20 was used to establish a reliability coefficient of 0.80. Treatment procedure mean, standard deviation and analysis of covariance were used for data analysis. The findings revealed that MIS specifically the regulatory self questioning strategy (RSQS) significantly enhanced the achievement of SS1 students in geometry more than the conventional method. Also there is no significant difference on the effect of RSQS on male and female students’ academic achievement in geometry. Based on the findings of the study, it was recommended among others that; Mathematics teachers should adopt RSQS when planning their lessons to enhance students’ interaction with each other and the learning materials to facilitate effective learning.